A DFT Study on Selected Physical Organic Aspects of the Fischer Carbene Intermediates [(M(CO)4(C(OMe)Me)] - Tareq Irshaidat (E-Journal of Chemistry)
Fischer carbenes are important starting materials for C-C bond formation via coupling reactions between carbene and wide variety of substituted alkenes or alkynes. This DFT study shed light on unique fundamental organic/organometallic aspects for the C(OMe)Me carbene in the free form and in case of bonding with M(CO)4 (M= Cr, Mo, W). The data illustrate that the structures of the title intermediates include a unique structure stabilizing intramolecular M…C-H interaction (agostic interaction). This conclusion was made based on calculated NMR data (for carbon and hydrogen), structural parameters, energy calculations of conformers (C-C conformation), selected IR stretching frequencies (C-O, C-C, and C-H), and atomic charges. The agostic interaction is most efficient in case of chromium and in general is described as an overlap between the σ-bond electron pair of C-H with an empty d-orbital of the metal. These characterized examples are new addition to the orbital interaction theory.